Effects of Vitamin D Supplementation on Pediatric Tuberculosis Clinical, Radiological, and Laboratory Outcomes - Khairiyadi, Khairiyadi; Hadi Putra, Nataniel; Marhaeni, Wulandewi; Himawan, Indra Widjaja; Panghiyangani, Roselina (Fakultas Kedokteran Universitas Brawijaya, 2025)
Tuberculosis is a systemic infectious disease caused by Mycobacterium tuberculosis. Pediatric tuberculosis patients often have reduced immunity due to malnutrition. Vitamin D supplementation improves host cell antimicrobial immune response, improving clinical outcomes. A study in Iran found that intramuscular cholecalciferol administration improved tuberculosis patients' outcomes, including weight gain and arm circumference when administered alongside tuberculosis therapy for 6 or 9 months. This study focuses on oral cholecalciferol for pediatric tuberculosis patients, analyzing its effects on clinical improvement, radiological features, laboratory findings, and its impact on weight gain, height, and vitamin D levels. The chi-square test was used to analyze the effect of vitamin D on the improvement of fever (p=0.638), cough (p=1.00), nutritional status (p=0.388), radiological features (p=0.510), decrease in leukocytes (p=1.00), lymphocytes (p=0.262), monocytes (p=0.575), and increase in vitamin D levels (p=0.149). The Mann-Whitney test was used to analyze the effect of vitamin D on the average increase in weight gain (p=0.392), height (p=0.044), vitamin D levels (p=0.770), and the average decrease in leukocytes (p=0.260), lymphocytes (p=0.055), and monocytes (p=0.687). The confidence level is 95%. Most clinical, radiographic, and laboratory outcomes in pediatric TB patients did not significantly change when vitamin D therapy was used. However, it markedly increased the patients' development, indicating possible advantages for these individuals.